2019
DOI: 10.1186/s12903-018-0702-4
|View full text |Cite
|
Sign up to set email alerts
|

BiodentineTM versus formocresol pulpotomy technique in primary molars: a 12–month randomized controlled clinical trial

Abstract: BackgroundThe objective of this clinical study was to prospectively compare the clinical and radiographic success rates of BiodentineTM pulpotomies versus formocresol pulpotomies in children vital primary molars.MethodsA randomized, split–mouth study design was used with a sample of 37 healthy children aged 4– to 8–year–old. A total of 56 pairs (112 teeth) of carious primary teeth, 1 pair per child, were selected for treatment. One tooth from each pair was randomly assigned to either the BiodentineTM pulpotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
3
25
1
6
Order By: Relevance
“…In this study, the high clinical outcome of FC agree with the success rate of FC reported by other investigators (47,52,53) , but it is not in agreement with the outcomes of other studies (54,55) .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study, the high clinical outcome of FC agree with the success rate of FC reported by other investigators (47,52,53) , but it is not in agreement with the outcomes of other studies (54,55) .…”
Section: Discussionsupporting
confidence: 55%
“…Our results revealed a 100% clinical success rate for both groups. This may be attributed to correct protocol, careful diagnosis with complete tooth isolation, and proper manipulation of the material under aseptic conditions (47) . Although a rare number of publications in the literature reporting on amnion pulpotomy, consistent with our survey, this outcome agrees with the study of Prasad et al (36) who reported 100% clinical success for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the comparison between FC and MTA [55,66,67,70,72,[76][77][78]85,86,88,90], yielded a better performance of the latter after 12, 24, 30 and 42 months of evaluation. Accordingly, El Meligy et al [87] observed slightly favorable clinical and radiographical outcomes of primary teeth underwent pulpotomy performed with BD than FC, although no statistically significant.…”
Section: Discussionmentioning
confidence: 97%
“…El Meligy et al [87] clinically and radiographically evaluated 108 primary teeth that underwent pulpotomy performed with BD or FC. After 12 months, the authors reported a 100% clinical success rate in both groups and a radiographic success rate of 100% and 98.1% in the BD and FC groups, respectively, although without any statistically significant difference.…”
Section: Biodentinementioning
confidence: 99%
“…Com o advento da tecnologia e inovação, muitos materiais capeadores estão sendo desenvolvidos e estudados para reparo e regeneração do tecido pulpar vital (Kuzum et al, 2015;Hugar et al, 2017;Kalra et al, 2017;Gopalakrishnan et al, 2019;Çelik et al, 2019;El Meligy et al, 2019 (Marques et al, 2014;Fernandes et al, 2015;Lourenço Neto et al, 2015;Lourenço Neto et al, 2016). (Marques et al, 2014;Fernandes et al, 2015;Lourenço Neto et al, 2015;Lourenço Neto et al, 2016 (Marques et al, 2014;Fernandes et al, 2015;Lourenço Neto et al, 2015;Lourenço-Neto et al, 2016).…”
Section: Introductionunclassified